Rethinking hydrocarbons build-up on urban roads: A perspective on volatilisation under global warming scenarios. (September 2019) - Wijesiri, Buddhi; Liu, An; Hong, Nian; Zhu, Panfeng; Yang, Bo; Zhao, Xu; Goonetilleke, Ashantha
Abstract: Stormwater is viewed as an alternative resource to mitigate water shortages. However, stormwater reuse is constrained due to the presence of many toxic pollutants such as hydrocarbons. Effective mitigation requires robust mathematical models for stormwater quality prediction based on an understanding of pollutant processes. However, the rise in global temperatures will impose changes to pollutant processes. This study has proposed a new perspective on modelling the build-up process of hydrocarbons, with a focus on volatile organic compounds (VOCs). Among organic compounds, VOCs are the most susceptible to changes as a result of global warming due to their volatility. Seven VOCs, namely, benzene, toluene, ethylbenzene, para-xylene, meta-xylene, ortho-xylene and styrene in road dust were investigated. The outcomes are expected to lay the foundation to overcoming the limitations in current modelling approaches such as not considering the influence of temperature and volatility, on the build-up process. A new conceptualisation is proposed for the classical build-up model by mathematically defining the volatility of VOCs in terms of temperature. Uncertainty in the re-conceptualised build-up model was quantified and was used to understand the build-up patterns in the future scenarios of global warming. Results indicated that for the likely scenarios, the variability in VOCs build-up gradually increases at the beginning of the dry period and then rapidly increases after around seven days, while the build-up reaches a near-constant value in a shorter dry period, limiting the variability. These initial research outcomes need to be further investigated given the expected impacts of global warming into the future. Graphical abstract: Image 1 Highlights: New concept proposed incorporating the influence of volatility on VOC build-up. Variability in VOC build-up increased rapidly after seven dry days. Higher temperatures reduce the variability in VOC build-up. More complex the chemical structure of VOC, the smaller the build-up variability. Build-up patterns of VOCs were projected under future scenarios of global warming. Abstract : Build-up of volatile organic components was investigated by taking temperature and volatility into account.